O trabalho preciso e precioso nas fábricas de semijoias em Limeira - SP : The precise and precious work in the semi jewel factories in Limeira - Sao Paulo - Silva, Marta de Mesquita, 1985- (2018)
Orientadores: Sandra Francisca Bezerra Gemma, Carlos Raul Etulain